TRANSSPLENIC DRAINAGE OF ABSCESSES AND POSTNECROTIC CYSTS OF TAIL OF PANCREAS - M. P. Korolyov; R. G. Avanesyan; E. A. Mikhailova (Вестник хирургии имени И.И. Грекова)
The authors designed and introduced into practice the method of percutaneous transsplenic drainage with single-stage installation of two drainages. The developed method allowed extension of indications for percutaneous drainage of liquid formations in the area of tail of pancreas in patients, whose the only possible way of mini-invasive percutaneous drainage was the transsplenic way. The method gives an option to apply this technique of percutaneous transsplenic catheter drainage of liquid formations in the area of tail of pancreas avoiding the more traumatic open methods of drainage.